2010
DOI: 10.1038/eye.2009.332
|View full text |Cite
|
Sign up to set email alerts
|

Axial length and intraoperative posterior vitreous detachment as predictive factors for surgical outcomes of diabetic vitrectomy

Abstract: Aims To evaluate the relationship of axial length (AXL), intraoperatively assessed posterior vitreous detachment (PVD) status, and surgical outcomes of diabetic vitrectomy. Methods Retrospective, consecutive case series. Clinical records were reviewed for 115 eyes (50 males, 65 females) with more than a 6-month follow-up who underwent diabetic vitrectomy from a single surgeon. Thirty-three eyes had vitreous haemorrhage, 37 had tractional retinal detachment (TRD) threatening the macula, 43 had TRD involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Previous studies have similarly reported that vitreoretinal adhesion is associated with an increased rate of postoperative TRD and poorer visual outcomes. 10,16 In contrast to these studies, which examined outcomes of vitrectomy for complications of PDR and included a broad range of surgical indications and coexisting ophthalmic diagnoses, our case series included only eyes with the primary diagnosis of NCVH with the aim of accurately identifying the prognostic value of PVD status in this subset of eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have similarly reported that vitreoretinal adhesion is associated with an increased rate of postoperative TRD and poorer visual outcomes. 10,16 In contrast to these studies, which examined outcomes of vitrectomy for complications of PDR and included a broad range of surgical indications and coexisting ophthalmic diagnoses, our case series included only eyes with the primary diagnosis of NCVH with the aim of accurately identifying the prognostic value of PVD status in this subset of eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of a shorter AL causing worse visual outcomes may be related to the tractional forces at the vitreoretinal interface caused by iERM. A previous study has shown that posterior vitreous detachment (PVD) is less frequently seen in eyes with a shorter AL in diabetic retinopathy patients 37 . Eyes with a shorter AL may have no PVD or macula-sparing PVD, which directly mediates vitreous tractional forces to the macula chronically (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This directly mediates the vitreous tractional force to the retina, and the preoperative tractional force by the iERM and/or the intraoperative tractional force exerted on the retina while peeling the iERM may damage the retinal neurons. Vitreous liquefaction is exacerbated in eyes with a long AL [23], and posterior vitreous detachment (PVD) is seen less frequently in eyes with a shorter AL in patients with diabetic retinopathy [24]. In contrast, PVD develops at a significantly younger age in highly myopic eyes compared to the age-and sex-matched non-highly myopic eyes [25].…”
Section: Discussionmentioning
confidence: 99%